Kappa antagonist to prevent drug relapse: does stage in addiction cycle matter? - Ridzwan, Irna Elina; Zulkifli, Muhammad Harith; Wasli, Nur Syafinaz; Syd Mohmad Faudzi, Syed Mohd Syahmi (International Islamic University Malaysia (IIUM), 2016)
Introduction: An upregulation of the kappa opioid receptor (KOR) system during preoccupation stage in addiction cycle will cause dysphoria among addicts which can lead to relapse. Therefore, KOR antagonism might hold the key to prevent relapse. In this study, we aim to identify the exact addiction's stage in which KOR antagonist can be given.